1984
DOI: 10.1002/1097-0142(19840501)53:9<1833::aid-cncr2820530905>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease with leptomeningeal involvement: Report of a case with long survival

Abstract: A 30‐year‐old white man with Stage IV B Hodgkin's disease, mixed cellularity type, developed leptomeningeal involvement shortly after relapsing on nitrogen mustard, Oncovin (vincristine), procarbazine, and prednisone (MOPP), and while receiving Adriamycin (doxorubicin), bleomycin, Velban (vinblastine), and dacarbazine (ABVD). Whole brain irradiation and intrathecal methotrexate were successfully incorporated into his treatment program. The patient has now been in complete remission for more than 40 months. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…8 Recurrent Hodgkin's disease or a second malignancy could show similar MRI abnormalities. 10 The absence of malignant cells on CSF cytologic examination, the slow and stabilizing course, and an unchanging MRI over time rule out malignant infiltration. 9 Furthermore, Hodgkin's disease is rarely associated with leptomeningeal dissemination.…”
mentioning
confidence: 99%
“…8 Recurrent Hodgkin's disease or a second malignancy could show similar MRI abnormalities. 10 The absence of malignant cells on CSF cytologic examination, the slow and stabilizing course, and an unchanging MRI over time rule out malignant infiltration. 9 Furthermore, Hodgkin's disease is rarely associated with leptomeningeal dissemination.…”
mentioning
confidence: 99%
“…Following radiotherapy, cytological analysis and cytocentrifugation of the patient's cerebrospinal fluid showed that there were no cells, whereas biochemical analysis showed an increase in microprotein levels and a decrease in the glucose level, suggesting leptomeningeal involvement. According to previous reports, remission can be achieved with intrathecal chemotherapy and cranial radiotherapy in patients with leptomeningeal involvement [15], although it was not achieved in the presented patient.…”
Section: Cranial Brain Magnetic Resonance Imaging (Mri)mentioning
confidence: 51%
“…There are few cases reported in the literature [13,[19][20][21][22][23], the biggest series of cases reported 6 patients [8].…”
Section: Discussionmentioning
confidence: 99%